Food Hygiene and Sanitation of the University Canteens in South Sumatra Province, Indonesia - Rahmiwati, Anita; Febry, Fatmalina; Etrawati, Fenny; Purnama Sari, Indah; Yeni, Yeni; Putri Sabila, Virgina; Prautami, Erike Septa; Maretalinia, Maretalinia (Kesmas, 2025)
Food safety is a critical public health issue, especially in institutional settings such as university canteens, where large populations are served daily. Inadequate hygiene and sanitation practices by food handlers can lead to foodborne illnesses, placing students and staff at risk. This study evaluated hygiene and sanitation conditions in the canteens of a leading public university in South Sumatra Province, Indonesia, known for its active food service facilities. This study examined food handlers’ knowledge, attitudes, and practices and assessed the microbiological safety of chicken curry by testing for Escherichia coli (E. coli) contamination and total plate count. Using a cross-sectional design, data were collected from 35 food handlers and 7 chicken curry samples across multiple canteens. Structured questionnaires and microbiological analysis were employed. Results revealed that although most food handlers demonstrated good knowledge and positive attitudes, 57.1% exhibited poor hygiene practices. Several chicken curry samples exceeded acceptable E. coli levels, indicating potential health risks. These findings underscore the urgent need for ongoing hygiene training, strict supervision, and standardized certification for food handlers to mitigate microbial hazards and ensure food safety in university settings.